Atypical Neurofibroma and Osteosclerotic Metastasis. (19th October 2011) - Varyani, Neeraj; Thukral, Anubhav; Garg, Sunny; Gupta, Kailash Kumar; Tandon, Ravi; Tripathi, Kamlakar
Abstract : 35-year-old male presented with multiple swellings in left leg, headache, weakness of limbs for 4 months, and blurring of vision for the last 15 days. On examination, he was pale, cachexic with generalized lymphadenopathy and lower motor neuron type weakness of limbs sparing right upper limb. Blood investigations showed anemia with high alkaline phosphatase. Chest radiograph revealed osteosclerotic metastatic lesion in humerus. Biopsy of leg lesion revealed atypical neurofibroma. Computed tomography (CT) of thorax revealed osteoblastic metastasis. Bone marrow aspiration showed cells with round to oval nuclei, fine granular chromatin with large central prominent nucleoli and eosinophilic cytoplasm with acini formation. Magnetic resonance imaging (MRI) of brain and spinal cord defined metastatic leptomeningeal deposits. Cerebrospinal fluid (CSF) cytology was positive for malignant cells. Gastroscopy showed an ulceroinfiltrative growth from stomach which on histopathology revealed diffuse adenocarcinoma. Palliative treatment was given with intrathecal methotrexate and systemic corticosteroid with chemotherapy. Patient's symptom improved drastically, but we lost him to followup.